The motivation of SPH journalists. - Chiam, Esther Shuen Ning. (2009)
This exploratory study examines the motivations of SPH journalists from a quantitative and qualitative research approach. There is scant research on Singapore journalism, and this study highlights some important motivators of local journalists. Of particular importance to the profession were influences of job autonomy, challenge, working relations, editor-reporter relationship, pay, and turnover. Generally, journalists are motivated more by “intrinsic” factors than by hygiene factors such as stress, pay and long hours. Hygiene factors are perceived to be part and parcel of the profession. The perception of journalists yielded some interesting findings. The third person effect, especially, seems to apply to Singapore journalists. While having a more positive image of themselves, they tend to be more negative in their perceptions of local journalists. From this pioneer research effort focused on Singapore journalism, many recommendations and suggestions for future research have been drawn.